Economic feasibility of building retrofitting mitigation potentials: Climate change uncertainties for Swedish cities. (15th May 2019) - Mata, Érika; Wanemark, Joel; Nik, Vahid M.; Sasic Kalagasidis, Angela
Highlights: Impact of future climate in mitigation and economic feasibility of retrofitting. Impact of uncertainties as location, energy system and household energy prices. Five climate scenarios, four Swedish cities, thirteen retrofitting measures. Decisions relying purely on cost-effectiveness will hinder energy retrofitting. Cost definitions and policies for buildings sector need to be revised. Abstract: Deep and rapid decarbonization of the building sector requires energy demand reductions and the incorporation of renewable-energy sources. Energy retrofitting of existing buildings is a central strategy in climate mitigation and has often been highlighted as a cost-effective strategy. However, decisions on these strategies are often hampered by modeling assessments that are limited by contextual, methodological, parametric, input, or output constraints. Here, we present a novel methodology to investigate the solid economic feasibility in building retrofit evaluations with mitigation measures. We first calculate the variations in the energy saving potentials and costs for 13 energy saving measures and five climate change scenarios. We then compare the obtained uncertainty due to a changing climate to other uncertainties, such as the boundaries for emission inventories and energy system development. Four cities in Sweden are modeled, which are responsible for half of the country's residential energy use. We find that the profitability of the retrofitting actions is primarily determined based on the annualized investments and energy saving potentials. Future climate has a less determinant role, with uncertainties similar to those of future consumer price development and fuel emission factors. Retrofits that only affect the energy need for space heating are more robust than changes in electricity usage. We conclude that strategies for building retrofitting should focus on prioritizing energy savings and mobilizing investments that may not be profitable based on the current techno-economic perspective.